2023
DOI: 10.1093/botlinnean/boac050
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of the Central Asian steppe-desert taxon Nitraria (Nitrariaceae) as revealed by integration of fossil pollen morphology and molecular data

Abstract: The transition from a greenhouse to an icehouse world at the Eocene-Oligocene Transition (EOT) coincided with a large decrease of pollen from the steppe-adapted genus Nitraria. This genus, now common along the Mediterranean coast, Asia and Australia, has a proposed coastal origin and a geographically widespread fossil record. Here we investigated the evolution, taxonomic diversity and morphological disparity of Nitraria throughout the Cenozoic by integrating extant taxa and fossil palynological morphotypes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…This approach differs from existing total evidence analyses of pollen, e.g. ( 42 ), in that our morphological features are continuous and quantitative, and the original molecular data are intrinsic to the selection of our phylogenetic embedding features and the training of our MLP neural networks. While this specific study uses a reference phylogeny derived exclusively from molecular data, the embedding model could utilize any well-supported tree, including total evidence phylogenies constructed using both molecular and morphological data.…”
Section: Discussionmentioning
confidence: 99%
“…This approach differs from existing total evidence analyses of pollen, e.g. ( 42 ), in that our morphological features are continuous and quantitative, and the original molecular data are intrinsic to the selection of our phylogenetic embedding features and the training of our MLP neural networks. While this specific study uses a reference phylogeny derived exclusively from molecular data, the embedding model could utilize any well-supported tree, including total evidence phylogenies constructed using both molecular and morphological data.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the timing of taxon radiations using fossil records spanning from approximately 430 Ma to 12 Ma (Supplementary Table 6). Furthermore, we assessed the diversity trajectories of ray-nned sh by evaluating 13,194 Actinopterygii fossil records (Supplementary Table 7).…”
Section: Mass Extinction and Tectonic Plate Movements Drove The Radia...mentioning
confidence: 99%
“…Diversity trajectory of sh using fossil sampling data A total of 13,194 Actinopterygii fossil records were used, of 9,841 were Teleostei fossil records (Supplementary Table 7). The were collected from the DeepBone database (https://www.deepbone.org).…”
Section: Annotation Of Protein-coding Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [45] considered that Nitraria first appeared between the Cretaceous and the Early Paleocene and hypothesized an Early Paleogene (65 Mya) origin of Nitraria based on molecular data. Amber Woutersen et al [46] found the oldest fossil pollen grain of Nitraria, at least 53 Myr old, and dated it to the Paleogene based on its characteristics. Reaumuria songarica is an ultra-xerophyte with strong stress resistance [47].…”
Section: Study Area and Species Distribution Surveymentioning
confidence: 99%